2020
DOI: 10.1002/tox.22996
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol induces osteoblast differentiation via angiopoietin1 and p38 MAPK

Abstract: In this study, we report the potential of cannabidiol, one of the major cannabis constituents, for enhancing osteoblastic differentiation in U2OS and MG‐63 cells. Cannabidiol increased the expression of Angiopoietin1 and the enzyme activity of alkaline phosphatase in U2OS and MG‐63. Invasion and migration assay results indicated that the cell mobility was activated by cannabidiol in U2OS and MG‐63. Western blotting analysis showed that the expression of tight junction related proteins such as Claudin1, Claudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
(91 reference statements)
3
7
0
Order By: Relevance
“…The MAPK family includes three isoforms: extracellular signaling regulatory kinase (ERK), c-jun amino-terminal kinase (JNK), and p38 kinase (p38 MAPK), which are involved in inflammatory processes ( 32 ). In our findings, LPS inhibited the activation of p38 MAPK signaling pathway, while CBD activated p38 MAPK signaling pathway in an inflammatory environment, which was consistent with previous studies showed that CBD promoted MG-63 cells osteogenesis differentiation through p38 MAPK pathways in non-inflammatory microenvironment ( 34 ). Canna-binoids and their correspondent receptors could activate downstream MAPK isoforms ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…The MAPK family includes three isoforms: extracellular signaling regulatory kinase (ERK), c-jun amino-terminal kinase (JNK), and p38 kinase (p38 MAPK), which are involved in inflammatory processes ( 32 ). In our findings, LPS inhibited the activation of p38 MAPK signaling pathway, while CBD activated p38 MAPK signaling pathway in an inflammatory environment, which was consistent with previous studies showed that CBD promoted MG-63 cells osteogenesis differentiation through p38 MAPK pathways in non-inflammatory microenvironment ( 34 ). Canna-binoids and their correspondent receptors could activate downstream MAPK isoforms ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…In rats, CBD was shown to improve fracture healing ( 48 ) and bone mineral density ( 49 ). Furthermore, CBD induced differentiation in two kinds of human osteoblast-like cell lines, demonstrating its potential to promote bone formation ( 50 ), as well as promoting osteogenic differentiation in bone marrow mesenchymal stem cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…6,32,33 Due to estrogen dysregulation, the overactivation of osteoclasts may lead to imbalance of bone resorption and formation during postmenopausal osteoporosis. 34,35 However, the modulatory mechanisms underlying osteoclast differentiation in osteoporosis remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a common bone disease, caused by environmental pollution, utilization of glucocorticoid, and estrogen dysfunction 6,32,33 . Due to estrogen dysregulation, the overactivation of osteoclasts may lead to imbalance of bone resorption and formation during postmenopausal osteoporosis 34,35 . However, the modulatory mechanisms underlying osteoclast differentiation in osteoporosis remain obscure.…”
Section: Discussionmentioning
confidence: 99%